2005
DOI: 10.4028/www.scientific.net/kem.291-292.287
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gas-Atomized Magnetic Tools

Abstract: The deficiency in the variety of available magnetic abrasive results in a narrow range of finishing performance. To break through this difficulty, this research developed iron-based gas-atomized magnetic tools. The magnetic tool has a spherical shape and micro-crevices on the surface. The micro-crevices perform the role of cutting instead of the edges of the existing magnetic abrasive, thereby achieving abrasive-less finishing. This paper studies the finishing performance of the developed magnetic tool. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Magnetic abrasive finishing, which utilizes magnetic force, is one of the most promising processes for the internal finishing of the capillary tubes, and it can achieve highly finished surfaces that conventional techniques never achieve [1,2,3,4]. Although previous research efforts have reported the development of several new magnetic abrasives [5,6,7,8,9,10,11], only iron-based composite powders containing alumina, which are produced by crushing a composite ingot obtained by thermite process of iron oxide and aluminium, are commercially used for internal finishing of capillary tubes at present. The conventional iron-based composite powders containing alumina has irregular shapes with sharp edges and a mean particle size of 80 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic abrasive finishing, which utilizes magnetic force, is one of the most promising processes for the internal finishing of the capillary tubes, and it can achieve highly finished surfaces that conventional techniques never achieve [1,2,3,4]. Although previous research efforts have reported the development of several new magnetic abrasives [5,6,7,8,9,10,11], only iron-based composite powders containing alumina, which are produced by crushing a composite ingot obtained by thermite process of iron oxide and aluminium, are commercially used for internal finishing of capillary tubes at present. The conventional iron-based composite powders containing alumina has irregular shapes with sharp edges and a mean particle size of 80 µm.…”
Section: Introductionmentioning
confidence: 99%